Statistical evaluation of the parameters of the parenchymatous organs on the basis of the model of the discrete scatterers - Skrypachenko, Z.M.; Radchenko, S.P. (Biophysical Bulletin, 2005)
With the help of the mathematical simulation, the physical bases of the processes of ultrasonic scattering by biological tissues are investigated. For a study, the model of soft tissues as the collection of the randomly distributed discrete scatterers was selected. In the work, the influence of the distribution of the cross-sections of scatterers, and also their sizes on the envelope of the obtained signal of response is evaluated. On the basis of the results of the computer, simulation has proposed the procedure of the reconstruction of the parameters of the parenchymatous organs and the method of determining the state of the tissue. In the work, it is also shown that on the basis of the model of discrete scatterers with the random parameters the classification and the identification of biological tissues can be carried out on the basis of their ultrasonic images.